The Effect of Book Tax Differences on Profit Growth (Empirical Study of Food and Beverage Companies Listed on the Indonesian Stock Exchange for the 2019-2023 Period) - Makmur, Aliya Nuraini; Mulyani, Sri; Rahmaniar, Ani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to analyze the effect of temporary differences on profit growth. The object of this research is food and beverage companies listed on the Indonesian Stock Exchange (BEI), with an observation period of 2019-2023. The data used in this research is based on annual financial reports obtained via the website www.idx.co.id The sampling method uses purposive sampling and the data analysis method uses quantitative analysis. As for the techniques used to test the accuracy of the data, the author uses classic assumption tests, namely normality test, heteroscedasticity test, autocorrelation test, multicollinearity test, multiple regression analysis. Correlation coefficient analysis, determination analysis, t test analysis and F test analysis. Using the SPSS 26 application. The test results for the Temporary Difference variable determined the calculated t value of 0.818 and a significant 0.417. so it can be calculated that the calculated t value < t table (0.818 < 1.669) and is significant 0.417 > 0.05. So it can be concluded that temporary differences have no effect on profit growth. The test results for the Permanent Difference variable found a calculated t value of 0.886 and a significant 0.380. so it can be calculated that the calculated t value < t table (0.886 < 1.669) and the significance is 0.380 < 0.05. So it can be concluded that permanent differences have no effect on profit growth. The results of this research show the results of simultaneous testing for the variables of temporary differences and permanent differences in finding a calculated f value of 0.812 and a significant 0.450. so it can be calculated that the calculated f value < f table (0.812 < 0.450) and is significant 0.450 > 0.05. So it can be concluded that temporary differences and permanent differences do not simultaneously influence profit growth.